Instilling Islamic Educational Values and the Exemplary Behavior of Kiai to Santri at the Darul Ishlah Kertek Islamic Boarding School - Rohayati, Sri; Sunarko, Asep; Nasokah, Nasokah (AJIRSS: Asian Journal of Innovative Research in Social Science, 2024)
This study aims to determine the application of the exemplary behavior of kiai in instilling Islamic educational values ​​at the Darul Ishlah Islamic Boarding School, Kertek District, Wonosobo Regency. This study uses a descriptive qualitative research method. This study observes the exemplary behavior of kiai in instilling the character of Islamic educational values ​​in santri. Data analysis shows that kiai at the Darul Ishlah Islamic Boarding School can instill Islamic educational values ​​in santri without violence. Supporting factors in the formation of student character are in the form of enthusiasm for learning, and inhibiting factors in instilling Islamic educational values ​​are in the background of santri.